Ultrasound-Guided Perineural Corticosteroid Injection for Lacertus Fibrosus Syndrome: A Retrospective Cohort Study - Greene C; Droppelmann G; García N; Jorquera C; Rosales J (Orthopedic Research and Reviews)
Cristóbal Greene,1,2 Guillermo Droppelmann,1 Nicolás García,1 Carlos Jorquera,3 Julio Rosales1 1Clínica MEDS, Santiago, Chile; 2Facultad de Medicina, Universidad Diego Portales, Santiago, Chile; 3Facultad de Ciencias, Escuela de Nutrición y Dietética, Universidad Mayor, Santiago, ChileCorrespondence: Guillermo Droppelmann, Clínica MEDS, Santiago, Chile, Email guillermo.droppelmann@meds.clBackground: The lacertus fibrosus serves as a site of entrapment for the proximal median nerve. Traditionally, surgical intervention has been the preferred method for resolution. This study demonstrates that perineural corticosteroid injection of the proximal median nerve entrapment under ultrasound guidance can improve nerve compression, strength, and pain in patients with lacertus fibrosus syndrome (LFS).Methods: A retrospective quasi-experimental cohort study without a control group following the STROBE guidelines was conducted from July 2020 to May 2023. The patient selection was carried out considering Elisabet Hagert’s diagnostic criteria. Ultrasound-guided proximal perineural corticosteroid injections were administered in the region of the lacertus fibrosus. Contingency tables were constructed to compare pre-and post-intervention data. The McNemar test was performed to evaluate the differences. Odds ratios (with 95% CI) were calculated to estimate the likelihood of improvement. A level of less than 0.05 was considered statistically significant. All analyses were performed using the R program.Results: Twenty-four patients with LFS (61% female, median age: 36 years), were analyzed. Significant improvements were observed in muscle strength perception for the flexor carpi radialis [OR: 33.0, 95% CI: 24.95– 41.0; p < 0.001], index flexor digitorum profundus [OR: 37.0, 95% CI: 29.0– 45.0; p < 0.001], and flexor pollicis longus [OR: 39.0, 95% CI: 31.0– 45.0; p < 0.001]. The scratch test positivity significantly decreased [OR: 4.56, 95% CI: 1.94– 15.67; p < 0.001], and pain levels were notably reduced [OR: 2.33, 95% CI: 0.97– 5.63; p < 0.001].Conclusion: Perineural corticosteroid injection under ultrasound guidance proved to be a minimally invasive approach for managing LFS. The intervention significantly improves muscle strength perception and reduces nerve compression and pain. These findings underscore the potential of this technique as a viable option for patients who have exhausted other therapeutic approaches before considering surgery.Level of Evidence: III cohort, treatment study.Keywords: interventional radiology, lacertus fibrosus syndrome, musculoskeletal ultrasound, ultrasound-guided infiltration